Maeropsis paphavasitae and Rotomelita longipropoda, two new species (Crustacea, Amphipoda) from Lower Gulf of Thailand. - Wongkamhaeng, Koraon; Coleman, Charles Oliver; Pholpunthin, Pornsilp (Zookeys, 2013)
Two new species of maerid and melitid Amphipoda, Maeropsis paphavasitae and Rotomelita longipropoda, respectively, collected from a seagrassbed of the Lower Gulf of Thailand, are described. Maeropsis paphavasitae is characterized by it seven teeth on the palm of gnathopod 2 and Rotomelita longipropoda can be recognized by its long gnathopod 1 propodus. Their characters are described and illustrated. All specimens are deposited at Princess Maha Chakri Sirindhorn Natural History Museum, Prince of Songkla University, Thailand and the Museum für Naturkunde, Berlin.

Melitid amphipods from the Gulf of Thailand, with a description of Dulichiella pattaniensis, a new species. - Wongkamhaeng, Koraon; Pattaratumrong, Manasawan Saengsakda; Puttapreecha, Ratchanee (Zookeys, 2014)
Two species of melitid amphipod were collected from the Gulf of Thailand. Dulichiella pattaniensis is new to science, and Melitalati latiflagella Ren & Andres, 2012 has not been previously reported from Thai Waters. Dulichiella pattaniensis is characterized by male gnathopod 2 distolateral crown with 4 spines; pleonite/urosomite formula 7-7-7-5-6-2; pereopod 5-7 dactylus with 2 accessory spines. This combination of characters has not been recorded previously in the Dulichiella. The characters of the specimens are described and illustrated. All specimens are deposited in the Princess Maha Chakri Sirindhorn Natural History Museum, Prince of Songkla University, Thailand.

Cheiriphotis trifurcata, new species (Crustacea, Amphipoda, Corophiidae, Protomedeiinae) from the Seagrass Bed of the Lower Gulf of Thailand. - Wongkamhaeng, K; Azman, B A R; Puttapreecha, R (Zookeys, 2012)
A new species of corophiid Amphipoda, Cheiriphotis trifurcata, collected from the seagrass bed of the Lower Gulf of Thailand, is described. Cheiriphotis trifurcata is characterized by its trifurcated tip of the modified setae on the outer ramus in male pleopod 3. In this paper, the new species is fully described and compared with related species and a complete key of the 16 valid species in the genus Cheiriphotis is given.

Shallow water marine gammaridean amphipods of Pulau Tioman, Malaysia, with the description of a new species. - Azman, B A R; Othman, B H R (Zookeys, 2013)
Eleven taxa including one new species of gammaridean amphipods are reported from the waters of Pulau Tioman. The presence of Tethygeneia sunda sp. n. represents the first record of the genus from the South China Sea. Additional material of Ampelisca brevicornis (Costa, 1853); Cymadusa vadosa Imbach, 1967; Paradexamine setigera Hirayama, 1984; Ericthonius pugnax (Dana, 1853); Leucothoe furina (Savigny, 1816); Microlysias xenokeras (Stebbing, 1918); Monoculodes muwoni Jo, 1990 are identified from the South China Sea, supporting previous records by Lowry (2000), Huang (1994), Imbach (1967), Margulis (1968) and Nagata (1959). Three additional species, Gitanopsis pusilla K.H. Barnard, 1916, Liljeborgia japonica Nagata, 1965b and Latigammaropsis atlantica (Stebbing, 1888), whilst previously reported from the neighbouring waters, comprise new records for the South China Sea.

Two new species of Urothoe (Crustacea, Amphipoda, Gammaridea) from the East Johor Islands Archipelago, Malaysia. - Azman, B A R; Melvin, C W H (Zookeys, 2011)
Two new species of urothoid amphipods from Pulau Sibu and Pulau Tinggi, Johor are described and illustrated. The specimens of Urothoe sibuensis new species were collected by vertical haul plankton net and is distinctively different from other existing Urothoe species by these combination of special characters; similar gnathopods 1-2 with short and stout propodus expanded into poorly defined palms; large eyes and epimeron 3 smooth. Urothoe tinggiensis new species as collected using an airlift suction sampler at seagrass area is characterized by its different gnathopodal configuration with setose dactylus of 5th pereopod; eyes minute; carpus is wider than merus in the 5th pereopod; subquadrate coxa 4; merus and carpus of pereopods 6-7 are linear.